'Brutalism Among the Ladies': Modern Architecture at Somerville College, Oxford, 1947-67. (2014) - Fair, Alistair
Abstract : In 1945, Janet Vaughan, a distinguished haematologist, became Principal of Somerville College, Oxford, her Principalship lasting until her retirement in 1967. Described in her obituary as 'a woman of extraordinary vitality and not a little impatience', Vaughan — awarded the DBE in 1957 — played a key role in steering the college through a period of major change in British Higher Education. Not least amongst the changes was a significant growth in the number of students at university across the country, which resulted in numerous, often high-profile, construction projects. Somerville, which had been founded in 1879 as the University of Oxford's second college for women, was not untouched by this development, and at Vaughan's retirement party, her colleague, the Nobel Prize-winning chemist Dorothy Hodgkin, referred to the several new buildings completed during the previous two decades. The college's post-war building campaign had begun modestly with two small infill developments by Geddes Hyslop in 1948–50 and 1954–56.